Dispersion‐assisted quick and simultaneous extraction of 30 pesticides from alcoholic and non‐alcoholic drinks with the aid of experimental design. Issue 7 (26th January 2018) - Jha, Rakesh Roshan; Singh, Nivedita; Kumari, Rupender; Patel, Devendra Kumar
Abstract: The presence of pesticides in food items and beverages is a big threat to humankind, and their quantitative estimation with high precision and accuracy is always a challenge for analytical chemists. Hence, a simple and rapid method is proposed for the simultaneous determination of 30 pesticides in beverages (alcoholic and non‐alcoholic drinks). The proposed method hyphenated with triple quadrupole liquid chromatography mass spectrometry has only 2 min chromatographic runtime for the analysis of all the pesticides. All the factors affecting the extraction yield have been optimized using an experimental design; and under optimized conditions, the developed method has been validated. The detection limits for all the pesticides were in the range of 0.001–0.348 μg/L with good linearity in the concentration range of 0.01–80.0 μg/L. The coefficient of determination was in the range of ( R 2 ) ≥ 0.977 to 0.999 for all the pesticides. The method was also checked for the precision of the relative standard deviation, which was below 4.75 (intra‐day) and 8.96% (inter‐day). The recovery of the method was 92–138%.